280 Effects of metabolizable energy and standardized ileal digestible lysine levels on lactating sow and litter performance. (30th November 2020) - Silva, Gustavo; Thompson, Robyn; Knopf, Brandon; Greiner, Laura L; Soto, Jose A; Vier, Carine; Lu, Ning; Orlando, Uislei
Abstract: The objective was to determine the effects of metabolizable energy (ME) and standardized ileal digestible (SID) lysine (Lys) levels on lactating sows and litter performance. A total of 600 sows (Camborough; PIC, Hendersonville, TN) were blocked by parity (P1, P2, P3+) on d 112 of gestation and allotted to 1 of 6 treatments arranged in a 2 x 3 factorial with the main effect of ME (3.2 and 3.4 Mcal/kg) and SID Lys (0.70, 0.85, and 1.00 %). Corn-soybean meal-based diets were fed from farrowing until weaning (d 21±2.3). Litters were cross-fostered until 48-h after farrowing to equalize litter size. Sows were weighed at d 112 of gestation and at weaning. Litter size and weight were collected at 24-h post-farrow and weaning. Daily feed intake was recorded from 48-h post-farrow until weaning. Data were analyzed using the GLIMMIX procedure of SAS with sow as the experimental unit. There was no evidence of interaction between ME and SID Lys for any response criteria. There was no evidence for an ME effect on sow performance. There was a quadratic effect (P< 0.05) of SID Lys on sow average daily feed intake, with the greatest intake at 0.85% SID Lys. Increasing SID Lys levels increased sow BW change (linear, P< 0.05). Litters from sows fed 3.4 Mcal of ME/kg had greater (P< 0.05) daily gain compared to those from sows fed 3.2 Mcal of ME/kg. Increasing SID Lys levels increased (linear, P< 0.05) litter weight at weaning and piglet daily gain. Wean-to-estrus interval, percentage of sows bred after weaning, total born on the subsequent parity, litter size at weaning, and percent of piglet removals were not influenced by dietary treatments. In summary, increasing ME levels did not affect sow performance, but improved litter and piglet daily gain. Increasing SID Lys levels improved both litter and sow performance.